CONSUMER PERCEPTION OF BRANDING IN EUROPEAN FOOTBALL - bansal, shivangi (2006)
Branding has become an increasingly popular form of marketing communication in all industries including the sports arena. Yet little has been researched in this field of branding and football remains an untouched subject of study. In this study, the concepts of brand equity and the determinants of customer-based brand equity in football have been looked at in the literature review and the focus is on how the consumers and fans perceive the subject of branding as being relevant to football. Data from a sample of 12 respondents, from different ethnic backgrounds, was collected through use of semi-structured interviews. Thereafter analysis and interpretation of the findings was undertaken using the categorization process. As this paper will show, football is now considered a brand among the big clubs only. To some extent, activities like merchandising and celebrity endorsement have taken over the excitement and passion of the game itself but the health of the game has not been adversely affected. Family tradition is one of the primary reasons that make consumers accept and follow particular clubs and hail them as brands. Clubs can leverage brand equity by capitalizing on catalyst factors like history, image and on-field success and this study reveals that Manchester United and Real Madrid have been successful in doing so. This research also highlights certain implications for marketers and paves the path for future research in this area of study.